ANALISIS FRAMING BERITA GUGATAN KE MAHKAMAH KONSTITUSI PASCA PEMILIHAN PRESIDEN 2024 DI MEDIA DETIK.COM DAN KOMPAS.COM - Farid Fakhrudin Akbar; Emilianshah Banowo (Cahaya Ilmu Bangsa, 2024)
This study aims to understand how Kompas.com and Detik.com framed news about the lawsuit to the Constitutional Court following the 2024 presidential election. The research utilizes Robert N. Entman's framing analysis method with a qualitative approach, focusing on four elements: define problem, diagnose causes, make moral judgement, and treatmentrecommendation. The study results indicate that the problem definition is the occurrence of fraud during the 2024presidential election contestation. The diagnosed causes include fraud occurring from upstream to downstream and issues with the constitution. Additionally, there are rebuttals stating that candidate pairs 01 and 03 had formal defects. The moral judgement involves support from various parties for each candidate pair to file and refute lawsuits during theConstitutional Court hearings. The treatment recommendation suggests that filing lawsuits and resolving disputes over results and processes in court is the proposed solution by each candidate pair.